A sketch of the Row in Parliament Street. - (:unkn) unknown (McLean, Thomas, 1829)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Great Britain -- Relations -- Ireland; Irish -- Caricatures and cartoons